2015
DOI: 10.1038/mtm.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic insulin gene therapy prevents diabetic enteropathy in STZ-treated CD-1 mice

Abstract: Depending on the population examined, from 6 to 83% of people with diabetes mellitus exhibit symptoms of altered gut motility, manifesting as dysphagia, reflux, early satiety, nausea, abdominal pain, diarrhea, or constipation. Hyperglycemia-induced cell loss within the enteric nervous system has been demonstrated in both diabetic rodents and patients with diabetes. Glycemic control is recommended to prevent diabetic gastroenteropathy but is often difficult to achieve with current treatment modalities. We asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(73 reference statements)
0
2
1
Order By: Relevance
“…Although ENS damage in diabetic animals has been reported in several studies, our results did not show significant changes in PGP9.5‐immunopositive cells in the ilea of rats 1, 4, 8, or 16 weeks after the induction of diabetes. Similar to our results, a previous study demonstrated that a longer period, up to 19 weeks, is necessary to cause total loss of neurons in the ilea of diabetic rats .…”
Section: Discussioncontrasting
confidence: 87%
“…Although ENS damage in diabetic animals has been reported in several studies, our results did not show significant changes in PGP9.5‐immunopositive cells in the ilea of rats 1, 4, 8, or 16 weeks after the induction of diabetes. Similar to our results, a previous study demonstrated that a longer period, up to 19 weeks, is necessary to cause total loss of neurons in the ilea of diabetic rats .…”
Section: Discussioncontrasting
confidence: 87%
“…A total of 90 pathogen-free healthy male CD-1 mice (weight 20-25 g, age 5 weeks) were purchased from Vital River Laboratory Animal Technology Co., Ltd (Beijing, China), and diabetes model was established in CD-1 mice via the injection of streptozotocin (STZ) as described previously (You et al, 2015). After two weeks of adaptive feeding, the mice were randomly divided into three groups: normal control group (NC group), diabetic group (DM group), and diabetic + RESV group (DR group).…”
Section: Animalsmentioning
confidence: 99%
“…About 20% of patients affected with longstanding diabetes are at risk of diarrhea or fecal incontinence [ 3 ]. Abnormal GI motility, in combination with irregular secretion and absorption leading to a decline in the contractile functional ability of the gut musculature as a result of loss of cells within the enteric nervous system [ 4 , 5 ], has been implicated as the main causal factor for these conditions [ 6 ]. Other factors such as mucosal inflammation could also contribute to disorders of the GI tract [ 7 ].…”
Section: Introductionmentioning
confidence: 99%